2004
DOI: 10.1128/jcm.42.5.2003-2012.2004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Excretion Patterns of Thermophilic Campylobacter spp. in Young Pet Dogs in Denmark

Abstract: The Campylobacter excretion patterns of 26 domestic pet dogs were described in a longitudinal study. The dogs entered the study between 3 and 8 months of age and were monitored until 2 years of age. They were tested monthly for Campylobacter carriage in stool samples that were cultured on the Campylobacter-selective media CAT and modified CCDA agar at 37 and 42°C. This study comprised 366 fecal swab samples, of which 278 (76.2%) were found to be Campylobacter positive, with the following distribution of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
103
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 36 publications
16
103
5
Order By: Relevance
“…In present study, the isolation rate of Campylobacter in dog was lower than that reported by Hald et al (76.2%) [15], however, it was similar to that of Tsai et al (13.9%) [31]. The isolation rate was significantly higher in stray dogs (25.2%) than household dogs (8.8%).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In present study, the isolation rate of Campylobacter in dog was lower than that reported by Hald et al (76.2%) [15], however, it was similar to that of Tsai et al (13.9%) [31]. The isolation rate was significantly higher in stray dogs (25.2%) than household dogs (8.8%).…”
Section: Discussioncontrasting
confidence: 55%
“…into their feces. Therefore, contact with the pets has been shown to be a risk factor for Campylobacter infections in humans and actual transmission has been demonstrated [15,29].…”
Section: Introductionmentioning
confidence: 99%
“…Hald et al . (2004) have created an accurate excretion pattern for thermotolerant C.  spp. and found that the rate of Campylobacter carriers in dogs during development increases from 60% in young animals of 3 months to nearly 100% in animals of 12 months and falls back to 67% at the age of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly detected species were Campylobacter upsaliensis ( C. upsaliensis) 39–98%, C. jejuni 1.2–51.2% and C. coli 0–9.8% (Hald et al . 2004; Koene et al . 2004; Keller et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria is frequently isolated both from animals with symptoms of enteritis and from healthy animals (Koane et al 2004). Dogs and cats often live in close proximity to humans, especially children, what brings probability of direct transmission of these pathogens (Hald et al 1997, Hald et al 2004.…”
mentioning
confidence: 99%